Variation in Mutant Prevention Concentrations - Gianvecchio, Crystal; Lozano, Natalie Ann; Henderson, Claire; Kalhori, Pooneh; Bullivant, Austin; Valencia, Alondra; Su, Lauren; Bello, Gladys; Wong, Michele; Cook, Emoni; Fuller, Lakhia; Neal, Jerome B.; et al. (Frontiers in Microbiology, 2019)
Objectives: Understanding how phenotypic traits vary has been a longstanding goal of evolutionary biologists. When examining antibiotic-resistance in bacteria, it is generally understood that the minimum inhibitory concentration (MIC) has minimal variation specific to each bacterial strain-antibiotic combination. However, there is a less studied resistance trait, the mutant prevention concentration (MPC), which measures the MIC of the most resistant sub-population. Whether and how MPC varies has been poorly understood. Here, we ask a simple, yet important question: How much does the MPC vary, within a single strain-antibiotic association? Using a Staphylococcus species and five antibiotics from five different antibiotic classes—ciprofloxacin, doxycycline, gentamicin, nitrofurantoin, and oxacillin—we examined the frequency of resistance for a wide range of concentrations per antibiotic, and measured the repeatability of the MPC, the lowest amount of antibiotic that would ensure no surviving cells in a 1010 population of bacteria. Results: We found a wide variation within the MPC and distributions that were rarely normal. When antibiotic resistance evolved, the distribution of the MPC changed, with all distributions becoming wider and some multi-modal. Conclusions: Unlike the MIC, there is high variability in the MPC for a given bacterial strain-antibiotic combination.